An evaluation of the wave energy resources in the proximity of the wind farms operating in the North Sea. (September 2021) - Rusu, Eugen; Rusu, Liliana
Abstract: The objective of the present work is to assess the wave power in the North Sea in the vicinity of the most relevant wind farms that are operating there. At this moment, the coastal environment of the North Sea is among the most significant areas in the world from the point of view of harvesting marine renewable energy. Furthermore, this area is also very relevant for offshore activities related to oil and gas extraction. From this perspective, its coastal environment would be a perfect candidate for the implementation of the wave projects, which would benefit from existing infrastructure. The ERA5 dataset has been considered for the evaluation of the wave power for the 30-year period (1989–2018). 10 reference points have been defined in the coastal environment of the sea covering the most relevant locations and for them, the mean wave power has been first assessed. After this, the seasonal and monthly variability of the wave power have been also evaluated together with some statistical parameters. The results show that the northern part of the sea has relatively significant wave energy resources and it can be a viable candidate for implementation of the future wave projects. However, the linear trends indicate a slight tendency of decrease of the wave power, but on the other hand, the coefficient of resource variation has small values. Finally, a comparison with the satellite data provided by the European Space Agency is also carried out for the 27-year period 1992-2018. While in general there is a very good concordance between the two datasets, for the reference points located in the north-eastern part of the sea, which are the most resourceful locations, the satellite data indicate higher values.